The Transformation of Rural Labour Systems in Colonial and Post-Colonial Northern Nigeria - Dirk Kohnert (Journal of Peasant Studies, 1986)
The study attempts to highlight the interrelation between three central points in the ongoing debate on the political economy of development: viability, surplus, and class-formation. A case study of the development of rural labour systems in Northern Nigeria is meant to provide both a better qualitative and quantitative idea of this interrelation. After an analysis of the socio-economic effects of forced and bonded labour during colonial times, the articulation of different systems of family and non-family labour has been investigated. Class-specific effects of labour and capital input do even result in an increasing use of communal labour by rich and middle peasants after the Nigerian Civil War: its form remains, but its content changes fundamentally. The socio-economic and material base for small-scale peasant subsistence production has been gradually destroyed. – – La transformation des systèmes du travail ruraux dans l'époque coloniale et post-coloniale dans le nord du Nigeria: L'étude tente de mettre en évidence l'interrelation entre trois points centraux dans le débat en cours sur l'économie politique du développement: la viabilité, surplus, et la formation de classe. Une étude de cas de l'évolution des systèmes de travail en milieu rural dans le nord du Nigeria est destiné à fournir à la fois une meilleure idée qualitative et quantitative de cette interrelation. Après une analyse des effets socio-économiques du travail forcé à l'époque coloniale et l'articulation des différents systèmes de travail de la famille et de travail non-familial a été étudiée. Effets spécifiques de l'apport travail et du capital, spécifique à une couche sociale, se traduisent même dans une utilisation croissante de main-d'œuvre collective par des paysans riches et moyens après la guerre civile nigériane: sa forme reste, mais le contenu se change fondamentalement. La base socio-économique et matériel de production paysanne de subsistance à petite échelle a été progressivement détruits.
Additional information: Author's version
Keywords: J81; N37; P48; Z13; F54; P16; P52; 330; labour systems; rural development; Nigeria; Africa; African History; Ländliche Entwicklung; Nigeria; Arbeitsorganisation; Subsahara-Afrika; Geschichte Afrikas; Kolonialismus